Dinamika Konstitusionalitas Undang-Undang Cipta Kerja Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 dan 54/PUU-XXI/2023 - Guswara, Arrafi Bima; Nasution, Ali Imran (JURNAL USM LAW REVIEW, 2023)
This research aims to examine the repairing Law no 11 of 2020 concerning Job Creation by issuance of Perppu No. 2 of 2022 concerning Job Creation and Questioning the constitutionality of Law no. 6 of 2023 after Constitutional Court Decision no. 54/2023. Constitutional Court Decision No. 91/2020 decides Law no. 11 of 2020 concerning Job Creation as Conditionally Unconstitutional and mandates law makers to improve it with meaningful community participation. The government took action to the decision by issuing Perppu no. 2 of 2022 concerning Job Creation. Constitutional Court Decision No. 54/2023 states the issuance of Perppu no. 2 of 2022 concerning Job Creation fits on UUD NRI 1945. Even though the Constitutional Court's decision is final and binding, it is considered to harm substantive justice in society. The research method applied is normative juridical research with a statutory approach and a case approach supported by primary and secondary legal materials which are then managed qualitatively. Previous research analyzed the constitutionality of the job copyright law based on Constitutional Court Decision no. 91/PUU-XVIII/2020, but this research analyzes the dynamics of the constitutionality of the job copyright law based on Constitutional Court Decision No. 91/PUU-XVIII/2020 and 54/PUU-XXI/2023. The results obtained from this research are, the issuance of Perppu no. 2 of 2022 concerning Job Creation which was subsequently enacted into Law no. 6 of 2023, againts Counstitutional Court Decision No. 91/2020, had requirement to provide meaningful participation, and was enacted into law when it no longer had any operational power. Constitutionality; Job Creation; Unconstitutional ConditionsPenelitian ini bertujuan untuk menilik perbaikan Undang-Undang Ciptaker terdahulu dengan menerbitan Perppu No. 2 Tahun 2022 tentang Cipta Kerja dan Menyoal dinamika konstitusionalitas UU No. 6 Tahun 2023 pasca Putusan MK Nomor 91/PUU-XVIII/2020 dan 54/PUU-XXI/2023. Putusan MK No. 91/PUU-XVIII/2020 memutus UU No. 11 Tahun 2020 tentang Cipta Kerja Inkonstitusional Bersyarat dan mengamanatkan pemerintah untuk memperbaikinya dengan partisipasi masyarakat secara bermakna. Pemerintah melaksanakan putusan tersebut dengan memilih menerbitkan Perppu No. 2 Tahun 2022 tentang Cipta Kerja dibandingkan dengan membentuk undang-undang. Putusan MK No. 54/PUU-XXI/2023 menyatakan Penerbitan Perppu No. 2 Tahun 2022 tentang Cipta Kerja tidak bertentangan dengan UUD NRI 1945. Meskipun Putusan MK bersifat final and binding tetapi dinilai mencederai keadilan substantif ditengah-tengah masyarakat. Metode penelitian yang diaplikasikan yaitu penelitian yuridis normatif dengan pendekatan perundang-undangan (statue approach) dan pendekatan kasus (case approach) yang didukung bahan hukum primer dan sekunder yang kemudian dikelola secara kualitatif. Hasil yang diperoleh dari penelitian ini yakni, penerbitan Perppu No. 2 Tahun 2022 tentang Cipta Kerja yang selanjutnya ditetapkan menjadi UU No. 6 Tahun 2023, tidak sejalan dengan amar Putusan MK No. 91/PUU-XVIII/2020, yang mensyaratkan keberadaan partisipasi masyarakat secara bermakna, dan ditetapkan menjadi undang-undang saat sudah tidak memiliki daya laku.